LIVING LAW DAN DINAMIKA SOSIAL: INTEGRASI NILAI-NILAI KEARIFAN LOKAL KE DALAM HUKUM NASIONAL - Siregar, Bismar (Sekolah Tinggi Ilmu Hukum Graha Kirana, 2025)
AbstractCustomary law exists in the form of traditions and societal habits, even though it is unwritten. Therefore, although customary law is not formally sanctioned by the state (not positivized), it is still implemented in the lives of the people. The validity of customary law is not always marked by the presence of sanctions but can be observed through expressions that reflect the community’s sense of justice in relation to customary law, particularly in the face of globalization, with a focus on efforts to preserve local cultural heritage. Globalization has a significant impact on traditional communities that continue to uphold their customary legal systems. This method emphasizes the normative aspect of law, namely the regulations issued by the government or legal bodies to govern public behavior. Collaborative efforts between indigenous communities, the government, and international institutions are necessary to formulate a legal framework that respects and supports indigenous rights while promoting sustainable development. Thus, the preservation of local culture can be maintained by integrating traditional values with global dynamics, enabling customary law to better reflect and accommodate the public’s need for justice, as a law that evolves in real practice within Indonesia’s positive legal system.AbtsrakHukum adat sebagai living law merupakan bagian integral dari sistem sosial masyarakat Indonesia yang pluralistik. Meskipun tidak dikodifikasi secara formal, hukum adat tetap hidup dalam praktik keseharian dan mencerminkan nilai-nilai keadilan lokal. Globalisasi dan modernisasi telah menimbulkan tantangan terhadap eksistensinya, terutama ketika sistem hukum nasional lebih mengutamakan pendekatan legalistik dan kodifikasi. Artikel ini menganalisis urgensi integrasi nilai-nilai kearifan lokal ke dalam hukum nasional secara konstruktif dan kontekstual. Dengan menggunakan pendekatan normatif dan konseptual, penelitian ini menegaskan pentingnya pengakuan formal terhadap hukum adat serta pembentukan mekanisme kelembagaan seperti pengadilan adat yang mendapat legitimasi negara. Integrasi hukum adat bukan hanya memperkuat identitas hukum nasional, tetapi juga memperluas cakupan keadilan substantif serta memberikan solusi alternatif dalam penyelesaian konflik, perlindungan hak asasi manusia, dan pembangunan hukum yang berkelanjutan.